The Effect of Intimate Friendship on Self-Disclosure Among Gen Z Users of The Close Friend Feature on Instagram - Raina Rahmadani; Lilis Ratnasari (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Close friend is an Instagram feature that individuals use to share posts only with a certain group of people. The selection of the close friend list is based on trust and close friendships. Currently, the close friends feature is more widely used by generation Z as a place to do self-disclosure in the form of photos and videos. This study aims to empirically test the effect of intimate friendship on self-disclosure in Gen Z users of the Instagram close friend feature. The sampling technique used in this study was purposive sampling and data analysis using simple linear regression techniques. The sample in this study consisted of 132 Gen Z with an age range of 14-29 years and actively uploading posts about themselves on Instagram close friends. The results of the simple linear regression analysis showed an F value of 57.104 and Sig. <0.001 (p <0.01) with an R square value of 0.305. From these results, the hypothesis is accepted, namely intimate friendship has a very significant effect on self-disclosure in Gen Z and intimate friendship contributes 30.5% to self-disclosure in Gen Z users of the close friendship feature.